Industrias extractivas, protesta indígena y consulta en la Amazonía peruana - Benavides, Margarita (2010)
This article analyzes the evolution of the natural resources tenure inthe Peruvian Amazon, and its relation with the indigenous protest ofthe years 2008 and 2009. The authoress argue that during the indigenousprotest aroused two opposite visions of development: the visionof the government supporting the big capital interests in one side,and the vision of the indigenous peoples defending their territoriesas a source of their material and identity survival. Nevertheless, theAwajún and Wampis suffered the disproportional repression of thegovernment in Bagua, with bloody results, the main four decreesthat were in the origin of the protest, because they threatened thejuridical security of indigenous peoples territories were derogated,and the indigenous peoples right to be consulted, established by theConvention 169 of the International Law Organization, was placed inthe center of the national debate. Nevertheless, the government hasresisted its application, because these consultations would imply aseries of socio environmental conditionings to the extractive industriesand the big scale infrastructure constructions. The authoresssustains that the conflict will continue if public policies in favor ofindigenous peoples would not be developed. For the establishmentof these public policies another vision of development is requiredfrom the State and government.